The Effect Of Financial Performance, Environmental Performance, Tax Avoidance, And Gender Diversity On Sustainable Development Goals (SDGs) - Novita Ayu Amalikhah; Slamet Haryono (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
The purpose of this study is to determine the influence of financial performance, environmental performance, tax avoidance, and gender diversity on sustainable development goals (SDGs). Based on the background and after deepening the literature, the researcher found a research gap from previous research that examined the relationship between the Company and the SDGs. Until now, research that connects the influence of financial, environmental, and diversity factors on achieving the SDGs is still minimal. Therefore, this study aims to analyze the influence of the current ratio, free cash flow, environmental performance, tax avoidance, and gender diversity in the board on the company's contribution to supporting the SDGs goals. This research is expected to contribute to academic literature and business practices related to the role of companies in sustainable development. This study uses a quantitative approach. The population in this study is all companies listed in the DES (Sharia Securities List) that have annual reports and sustainability reports for the 2021-2023 period. The sampling technique used in this study is purposive sampling. The sample in this study is 70 companies. The data collection technique in this study is using documentation techniques. The hypothesis test in this study uses the formula 1) T-test, 2) F-test, and 3) Determination Coefficient Test. Based on the results of the data analysis processed and the discussion that has been described by the researcher, the following conclusions are reached: 1) The current ratio of companies has a positive effect on the SDGs. This is because companies that show greater liquidity and profitability tend to have the necessary resources to support the SDGs. 2) Free cash flow does not influence the SDGs. This can happen because free cash flow only shows the availability of funds, and how the funds are used. 3) Environmental performance has a positive effect on the SDGs. This can happen because by increasing environmental performance, companies can help support the global goals (SDGs) related to environmental sustainability. 4) Tax avoidance carried out by companies will hurt the SDGs. This is because taxes are one of the largest revenues owned by the state. 5) Board gender diversity has a positive influence on the SDGs. This happens because the level of equality in the board can encourage an inclusive work culture and will have an impact on company productivity.